Designing a Financial Mathematical Task for Vocational High School Using Saving and Stock Context - Ramadhan, M. Hasbi; Zulkardi; Putri, Ratu Ilma Indra; Resti, Yulia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
In daily life, banks usually not only offer their saving programs but also their stocks. This research focuses on designing a financial mathematical task for vocational high school (VHS) which is valid, practical, and has potential effects using saving and stock context. Pendidikan Matematika Realistik Indonesia (PMRI) is the approach used in this research. For the method, we used design research with a type of development studies. This research was conducted at VHS 1 at Jambi City with research subjects were the eleventh-grade students of accounting major. This research produces three financial mathematical tasks with the context of saving and stock. The results of research also found that by using saving and stock context, students became more understanding of real-world problems and wise in making decisions regarding financial problems. This research can also be used as a reference for financial mathematics teaching materials, especially for vocational high school teachers.